Penerapan Metode MOORA Untuk Menentukan Shampoo Terbaik Bagi Kulit Berketombe Pada Perempuan - Yumni Syabrina Agustina Lubis; Laila Kumalasari; Fikri Wicaksono; Irfan Sudahri Damanik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Scalp dandruff is a common problem experienced by women and can cause discomfort and lower self-confidence. The large number of shampoo products on the market often makes it difficult for consumers to choose the product that best suits their scalp condition. This study aims to apply the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method to determine the best shampoo for women with dandruff. The problem faced is choosing an effective and safe shampoo for scalp dandruff, by considering various criteria such as price, active ingredients, and effectiveness in treating dandruff. This study uses predetermined criteria and calculates the weight of each criterion based on user preferences. Using the MOORA method, available shampoo alternatives are evaluated and ranked to find the optimal product. The results show that the MOORA method can provide objective and effective results in the decision-making process. With this system, it is hoped that consumers can more easily choose the appropriate shampoo, and assist manufacturers in improving product quality according to market needs. The research results show that the MOORA method can provide the right solution in choosing the best shampoo based on various factors, so that it can help consumers in making more informed and objective decisions.